A Case Report of Intraoperatively Diagnosed Cholangiocarcinoma after Unsuccessful Conservative Treatment of ERCP Complicated with Hemorrhage - Bozinovska Beaka, Gordana; Prgova Veljanovska, Biljana; Zdravkovska, Milka; Burova, Blagica (Lietuvos chirurgija, 2018)
[full article, abstract in English; abstract in Lithuanian]BackgroundCholangiocarcinoma is a malignant tumor arising from the epithelium of the bile ducts. Most of these tumors are adenocarcinomas [1]. Intrahepatic cholangiocarcinoma accounts for 10% of all cholangiocarcinomas, hilar cholangiocarcinoma for 25%, and extrahepatic cholangiocarcinoma for 65% [2, 3]. Cholangiocarcinoma can develop in any part of the extrahepatic duct, occurring in 50–75% of reported cases in the upper third of the duct including the hepatic hilum, in 10–25% in the middle third, and in 10–20% in the lower third [4–6]. Approximately 95% of cases show extrahepatic obstruction at the time of diagnosis [7]. In a meta-analysis of 21 prospective trials, the rate of hemorrhage as a complication of ERCP was 1.3% (95% CI, 1.2%–1.5%) with 70% of the bleeding episodes classiﬁed as mild [8]. Hemorrhagic complications may be immediate or delayed, with recognition of occurring up to 2 weeks after the procedure. The risk of severe hemorrhage (ie, requiring >5 units of blood, surgery or angiography) is estimated to occur in fewer than1 per 1 000 sphincterotomies [9]. Despite new and advanced diagnostic methods, sometimes this type of tumor is finally diagnosed from pathological findings on excised tissue.Case reportWe present one case with cholangiocarcinoma diagnosed after surgical treatment of hemorrhage as post procedural complication from ERCP. With MRCP intraluminal stenosis of the upper part of common bile duct has been noticed and suspicious presence of substrate with consecutive dilatation of the upper billiary tract. ERCP was performed and sphincterotomy have been made without evacuation of any intraluminal substrate from common bile duct. Insufficient ERCP cholangiography was made and biopsy of the part with stenosis could not be taken due to permanent bleeding from performed sphincterotomy.Despite all attempts for conservative treatment of the hemorrhage, patient was still with permanent decreases of hemoglobin levels and with persistent hemorrhagic anemia. With decision from medical council the patient has been transferred to the Department of abdominal surgery for further immediate surgical treatment.ConclusionPatient with extrahepatic bile duct carcinoma initially diagnosed as a calculus in the common bile duct. Looking back, the patient had symptoms which differential diagnosis for bile duct cholangiocarcinoma should be established. Clinical symptoms such as right hypochondrium pain, itchy skin, vomiting and diarrhea. The laboratory findings showed constantly elevated bilirubin and liver enzymes also elevated tumor markers as CA19-9 and CEA. Hemorrhage that occurs after ERCP sphincterotomy and attempt for biopsy could not been controlled with conservative measures. Patient with consequently caused hemorrhagic anemia has been transferred for surgical treatment, which stopped the bleeding, made final diagnosis and treatment of proximal stenosis of common bile duct.
Keywords: cholangiocarcinoma, ERCP hemorrhage, billiary stenosis